On the Association Between Demographic Structural Change and the Effectiveness of Nurse Staffing Policy for Inpatient Care: Evidence from Taiwan - Lai YL; Chen WY; Lee SS; Liaw YP (Dove Medical Press, 2024)
Yi-Ling Lai,1,2 Wen-Yi Chen,3,* Shiuan-Shinn Lee,1,* Yung-Po Liaw1,4,5 1Department of Public Health and Institute of Public Health, Chung Shan Medical University, Taichung, 402367, Taiwan; 2Community Health Center, Taichung Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, Taichung, 427213, Taiwan; 3Department of Senior Citizen Service Management, National Taichung University of Science and Technology, Taichung, 403301, Taiwan; 4Department of Medical Imaging, Chung Shan Medical University Hospital, Taichung, 402367, Taiwan; 5Institute of Medicine, Chung Shan Medical University, Taichung, 402367, Taiwan*These authors contributed equally to this workCorrespondence: Wen-Yi Chen, Department of Senior Citizen Service Management, National Taichung University of Science and Technology, 193 Sec 1, San-Min Road, Taichung, 403301, Taiwan, Tel +886 4 22196932, Email chenwen@nutc.edu.tw Shiuan-Shinn Lee, Department of Public Health, Chung Shan Medical University, 110, Section 1, Jianguo North Road, Taichung, 402367, Taiwan, Tel +886 4 24730022 Ext 12185, Email shinn@csmu.edu.twPurpose: This study investigates the influence of demographic changes on the effectiveness of hospital nurse staffing policy, measured by the cumulative response of inpatient care quality to adjustments in hospital nurse staffing levels in Taiwan.Methods: The research design utilized in this study aligns with the observational time-series methodology, and a total of 99 monthly time-series observations were collected from multiple databases administered by the Taiwan government over the period from January 2015 to March 2023. Specifically, the time-varying parameter vector autoregressive and autoregressive distributed lag models were employed to investigate the association between age distribution and nurse staffing policy effectiveness.Results: The time-varying impulse responses of the unplanned 14-day readmission rate after discharge to changes in nurse staffing levels indicate a positive association between patient-to-nurse ratios and unplanned 14-day readmission rates across various types of hospitals. Nevertheless, the effectiveness of hospitals' nurse staffing policy is observed to diminish with population aging, particularly evident in medical centers and regional hospitals.Conclusion: Policymakers should establish lower mandated patient-to-nurse ratios, grounded in practical nurse workforce planning, to address the needs of an aging society and enhance inpatient care quality through improved nurse staffing in hospitals.Keywords: demographic structural change, nurse staffing, inpatient care quality, time-varying parameter vector autoregressive model, autoregressive distributed lags model